Persepsi Siswa Sekolah Dasar terhadap Mata Pelajaran Matematika saat Pandemi Covid-19 - Jalal, Novita Maulidya (Pedagogik Journal of Islamic Elementary School, 2022)
This study aimed to describe the perception of elementary school students toward Mathematics Subjects during the Covid 19 Pandemic. The research design used was descriptive quantitative. The population in this study were fifth-grade students at Y Elementary School in Makassar, with a sample of 4 fifth-grade subjects who were willing to be interviewed related to research and conducting online learning. The data collection technique used questionnaires and was deepened by interviews. The data analysis technique used is the percentage technique. The results showed that 50% of the subjects had a perception of mathematics as a fairly difficult subject. 75% of the subjects considered Mathematics to be important, and 50% of the subjects had an experience obtaining low scores in Mathematics. Furthermore, the subjects generally stated that they had more difficulty understanding the material. Mathematics lessons while studying online during the pandemic 19. Efforts are being made by asking parents at home and teachers.